ANALISIS KEPEMIMPINAN KEPALA SEKOLAH DALAM IMPLEMENTASI TOTAL QUALITY MANAGEMENT DI MADRASAH ALIYAH NEGERI KARIMUN - Sumarno; Taufiqurrahman; Hikmatul Hidayah (As-Sulthan Journal of Education, 2025)
Improving the quality of education continues to be a top priority, both by the government and by all parties involved in the world of education. To achieve this goal, every educational institution, including secondary schools, is required to be able to implement effective and efficient management. This research aims to analyze the leadership of school principals in implementing Total Quality Management at MAN Karimun. This research was carried out at MAN Karimun. This research uses a qualitative research approach with descriptive methods using interviews and direct observation at schools. The results of this research explain that with transformational leadership, school principals inspire all madrasa elements to innovate and work towards a shared vision. A collaborative approach ensures decision making involves multiple parties, creating a sense of collective responsibility. Meanwhile, servant leadership is demonstrated through the principal's attention to the needs of students, teachers and staff to create a comfortable learning environment. The positive impact of this leadership can be seen from improving the quality of education and achievement of MAN Karimun students.